Characterization of adult T-cell leukemia/lymphoma patients with specific skin lesions in a tertiary dermatological service in Brazil - Valente, Mariana; Sanches, José Antonio; Nukui, Youko; Cury-Martins, Jade; Souza, Bruno Castro; Pereira, Juliana; Miyashiro, Denis (Frontiers in Medicine, 2025)
IntroductionHuman T-lymphotropic virus type-1 (HTLV-1) is endemic in some countries, including Brazil. HTLV-1 is the etiological agent of adult T-cell leukemia-lymphoma (ATLL), a rare and aggressive CD4+ T-lymphocyte malignancy. ATLL affects 1–5% of virus carriers. Dermatological involvement occurs in 40–70%. Diagnosis is based on clinicopathologic correlation and HTLV-1 serology. There are few therapeutic options so far.MethodsThis is an observational retrospective cohort study with ATLL patients followed in a tertiary hospital in São Paulo, Brazil. Data were collected at diagnosis. Survival curves using the Kaplan–Meier method were analyzed with log-rank test, univariate and multivariate analyses were performed with the Cox proportional hazards model.ResultsForty-four patients were studied, 24 females (54.5%), and 20 males (45.5%). The median age at diagnosis was 59.4 years. Classification at diagnosis was: 16 (36.4%) chronic (93.7% unfavorable, 6.2% favorable), 14 (31.8%) acute, 10 (22.7%) smoldering, four (9.1%) lymphoma, and none with primary cutaneous tumoral. Regarding skin lesions, 18 (40.9%) had plaques; 15 (34.1%) nodules/tumors; 11 (25.0%) papules; 10 (22.7%) erythroderma; seven (15.9%) patches; two (4.5%) ichthyosis; one (2.3%) purpuric lesions. Epidermotropism/exocytosis of lymphocytes was observed in 25 patients (62.5%), and Pautrier microabscesses in three (7.3%). Four patients (10.0%) had subcutaneous involvement, two (5.0%) folliculotropism, two (5.0%) angiocentrism, and one (2.5%) perineural involvement. Ten patients (25.0%) presented a lichenoid pattern. Thirty-four patients (79.1%) had increased lactate dehydrogenase; 20 (45.5%) lymphocytosis; six (13.6%) flower cells in peripheral blood; six (14.6%) hypercalcemia; five (12.2%) hypoalbuminemia. Beta-2 microglobulin was increased in all 24 cases investigated. Monoclonal T-lymphocytes were observed in the blood of 23 patients (76.7%) and the skin of 19 (76.0%). Thirty patients (68.2%) died. Median overall survival was 32.3 months. Acute and chronic unfavorable forms had worse prognoses, with median overall survival of 23.3 and 34.1 months, respectively (p = 0.0011). After multivariate analysis, Shimoyama classification (acute) and urea levels were associated with poorer prognoses.ConclusionWe described a large Brazilian cohort of ATLL with cutaneous involvement. Description of clinical, pathology, laboratory, and follow-up data, and factors associated with poorer survival is essential to provide better care and to improve the quality of life of these patients.